Cybersecurity Trends in Digital Marketing for Public Health: A PRISMA based Bibliometric Analysis - Sakib, Nazmus; Faraji, Mahfujur Rahman; Shovon, Fatihul Islam; Naiem, Md. Julker; Hossain, MD. Tofajjal; Mim, Taslima Akter; Shanta, Sadia Arfin (Asosiasi Doktor Sistem Informasi Indonesia, 2025)
This study conducts a bibliometric analysis of digital marketing in public health through the lens of cybersecurity, aiming to evaluate research trends from 2015 to 2025. It identifies key developments, major contributors, and provides guidance for future studies. A total of 1,191 documents were analyzed, revealing a significant annual growth rate of 32.01% and an average of 19.01 citations per document. The analysis explores how digital marketing for public health intersects with cybersecurity, a domain that remains underexplored. Data collection and visualization were conducted using Scopus, Biblioshiny, and VOSviewer, with article selection guided by the PRISMA methodology. Results indicate consistent growth in publications over the decade, though a noticeable decline occurred post-COVID-19 in 2020. The study offers a comprehensive mapping of existing literature and highlights the strategic importance of integrating cybersecurity into digital health marketing to protect patient data, maintain public trust, and enhance health outcomes. It provides valuable insights for researchers, policymakers, and practitioners aiming to improve the security and effectiveness of digital health communication in an increasingly connected world.